Pengembangan E-Authentic Asessment Berbasis PBL untuk Meningkatkan Kompetensi Mahasiswa dalam Pembelajaran Jaringan Komputer - Ambiyar; Raimon Efendi; Waskito; Surfa Yondri; Yuyun Irawati (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
This study aims to develop authentic online assessment instruments based on problem based learning. Authentic assessment instruments will be accessed online in computer network learning to measure student competencies effectively and efficiently. Type of research is research and development and used refer to the 4 D model (define, design, develop, disseminate). The analysis technique uses the Aiken'V test, and validity uses expert testing and Focus Group Discussion (FGD). The practicality test is carried out by applying the product to students in the form of a product practicality questionnaire and to test the effectiveness using basic time series design. Validity test results show the RPS and instruments developed are valid with Aiken's V values ​​of 0.708 and 0.716. Practicality test results on the practicality test by lecturers and students on the RPS were 93% and authentic assessment 91%. Effectiveness test results with time series analysis were 38% with the effective category. The implication of the study is that there is a positive effect on learning outcomes, the value of students completeness increases and the gain score test is 0.38 in the medium category. The findings of this study have resulted in e-authentic assessment instruments with valid, practical and effective categories.